Impaired Reorganization of Centrosome Structure Underlies Human Infantile Dilated Cardiomyopathy. Issue 17 (27th March 2023) - Chun, Young Wook; Miyamoto, Matthew; Williams, Charles H.; Neitzel, Leif R.; Silver-Isenstadt, Maya; Cadar, Adrian G.; Fuller, Daniela T.; Fong, Daniel C.; Liu, Hanhan; Lease, Robert; Kim, Sungseek; Katagiri, Mikako; et al.
Abstract : Background: During cardiomyocyte maturation, the centrosome, which functions as a microtubule organizing center in cardiomyocytes, undergoes dramatic structural reorganization where its components reorganize from being localized at the centriole to the nuclear envelope. This developmentally programmed process, referred to as centrosome reduction, has been previously associated with cell cycle exit. However, understanding of how this process influences cardiomyocyte cell biology, and whether its disruption results in human cardiac disease, remains unknown. We studied this phenomenon in an infant with a rare case of infantile dilated cardiomyopathy (iDCM) who presented with left ventricular ejection fraction of 18% and disrupted sarcomere and mitochondria structure. Methods: We performed an analysis beginning with an infant who presented with a rare case of iDCM. We derived induced pluripotent stem cells from the patient to model iDCM in vitro. We performed whole exome sequencing on the patient and his parents for causal gene analysis. CRISPR/Cas9-mediated gene knockout and correction in vitro were used to confirm whole exome sequencing results. Zebrafish and Drosophila models were used for in vivo validation of the causal gene. Matrigel mattress technology and single-cell RNA sequencing were used to characterize iDCM cardiomyocytes further. Results: Whole exome sequencing and CRISPR/Cas9 gene knockout/correction identified RTTN, the gene encoding the centrosomal protein RTTN (rotatin), as the causal gene underlying the patient's condition, representing the first time a centrosome defect has been implicated in a nonsyndromic dilated cardiomyopathy. Genetic knockdowns in zebrafish and Drosophila confirmed an evolutionarily conserved requirement of RTTN for cardiac structure and function. Single-cell RNA sequencing of iDCM cardiomyocytes showed impaired maturation of iDCM cardiomyocytes, which underlie the observed cardiomyocyte structural and functional deficits. We also observed persistent localization of the centrosome at the centriole, contrasting with expected programmed perinuclear reorganization, which led to subsequent global microtubule network defects. In addition, we identified a small molecule that restored centrosome reorganization and improved the structure and contractility of iDCM cardiomyocytes. Conclusions: This study is the first to demonstrate a case of human disease caused by a defect in centrosome reduction. We also uncovered a novel role for RTTN in perinatal cardiac development and identified a potential therapeutic strategy for centrosome-related iDCM. Future study aimed at identifying variants in centrosome components may uncover additional contributors to human cardiac disease.